Educación, Libertad y Justicia en Fichte - Arrese Igor, Hector Oscar (2017)
In this paper, I explore two fundamental dimensions of the Fichtean conceptualization of freedom. First, I describe the intimate relationship that Fichte established between freedom and property. In doing this, I try to reconstruct the justification of the right to earn a living from the own work as a necessary condition of freedom. Second, I offer an account of learning skills as another central condition of freedom in order to reconstruct Fichte’s demonstration of the need of recognizing the other. Last, I derive the implications of Fichte’s idea of recognition in order to design an education policy.